Isolation and identification of microorganisms causing clinical mastitis using AccuMast® plate - de Sousa, Francielle; Pereira de Melo, Alex; de Oliveira, Amauri Marcelino; Silva Rabelo, Michel; Freitas Ribeiro, Laryssa (Pubvet, 2020)
In the current world agricultural scenario, Brazilian dairy farming stands out as an emerging power, due to technological advances and economic importance. Throughout the dairy production chain, these advances are aimed at increasing production and the search for quality, highlighting the importance of studying microbiological cultures, thus enabling identification, growth potential, multiplication and related research on certain microorganisms that cause mastitis in the herd. The objective, therefore, is to show that bacteriological identification using AccuMast® plates enables better decision making in relation to the treatment of clinical mastitis. The work was carried out from January 2018 to October 2019, on a property in the city of Conquista - Minas Gerais, in the Triângulo Mineiro region. All cows with mastitis had their milk collected individually from each roof, and submitted to the black-bottomed mug test process. The samples were inoculated into AccuMast® plates, and the interpretation of the plate result is done by changing the color of the growth of pathogens in the culture medium. All results were evaluated monthly comparing the results with the previous ones. Assessing the reading of the plates and data, it was observed that 46.69% of animals that were diagnosed with clinical mastitis, by the dark-bottomed mug test, did not require treatment with antibiotics, as no pathogenic agent was identified. Furthermore, in the 53.31% of the remaining animals, highly contagious and rapidly disseminating microorganisms causing mastitis were identified, such as Streptococcus galactite, Streptococcus uberis and Staphylococcus aureus. In short, the AccuMast® plate, allows the identification of the pathogenic agent, favoring the appropriate decision making regarding the use or not of treatment, and provides better elaboration of the antimicrobial therapy according to each pathogenic agent.
Keywords: pathogens; cattle; microbiology; milk; public health